2014
DOI: 10.1021/ma500240v
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for an in Situ Developed Polymer Phase in Ionic Elastomers

Abstract: The overall mechanical performance of ionic elastomers, such as carboxylated nitrile rubber (XNBR), is largely governed by ionic clusters formed during the cross-linking of the elastomers with zinc oxide. These ionic aggregates promote microphase separation and show additional high-temperature relaxation behavior in dynamic mechanical analysis. In this study, the nature of these ionic aggregates is explored for the first time. We find that some zinc-containing compounds, such as zinc–aluminum-layered double hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
73
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 48 publications
3
73
0
Order By: Relevance
“…However, when sufficient time was given up to 240 h, intensity of the peaks found to increase significantly. This trend confirms the labile and reversible nature of the ionic phase [31]. On close observation, it can be seen that the intensity is indeed more than the unheated original sample itself, probably due to the enhanced reordering of the ionic structure consequent to the re-alignment of the macromolecules upon heating to 150°C.…”
Section: Investigation Of Ionic Transition By Xrdsupporting
confidence: 65%
“…However, when sufficient time was given up to 240 h, intensity of the peaks found to increase significantly. This trend confirms the labile and reversible nature of the ionic phase [31]. On close observation, it can be seen that the intensity is indeed more than the unheated original sample itself, probably due to the enhanced reordering of the ionic structure consequent to the re-alignment of the macromolecules upon heating to 150°C.…”
Section: Investigation Of Ionic Transition By Xrdsupporting
confidence: 65%
“…Figure (a) demonstrates the MDR rheographs for the different rubber composites cured at 160 °C until 1 h, and therein, the XNBR–ZnO specimen clearly shows the highest uniform rheometric torque ~6 dNm among all other specimens that contain ZnSt. This is attributably due to the formation of zinc carboxylate ionic linkage in the XNBR–ZnO that considerably raises its elastic modulus . Further, it can be seen from this figure that the addition of ZnSt to XNBR–ZnO had the effect of significantly lowering the elastic modulus initially.…”
Section: Resultsmentioning
confidence: 82%
“…Some of the present authors have previously shown that XNBR, a functional elastomer can also form ionomeric polymer composites and the microstructure of these composites could be resembled with ionomeric shape memory composite particularly, when treated with zinc oxide …”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations